Labour inspection. A workers' education manual (Geneva, 1986)
"ILO pub. Workers education teaching aid on labour inspection - traces the historical background of labour inspection and the role of ILO in its development; describes functions and systems of labour inspection, powers and duties of labour inspectors, relations between labour inspection and other services of labour administration, employers organizations and trade unions, etc.; includes texts of ILO conventions nos. 81 and 129 and ILO recommendations nos. 81 and 133. References."